Microsatellite Instability and Colorectal Cancer, Immunohistochemical and Molecular Evaluation by Using DNA Sequencing: A Single Center Experience - Bita Geramizadeh; Farzaneh Bozorg-Ghalati; Firoozeh Jafari; Mitra Mirzai; Zahra Jowkar (Iranian Society of Pathology, 2021)
Background & Objective: Microsatellite instability is common in familial colorectal cancers. It can be tested by the molecular and immunohistochemical methods. There are very few studies which address comparing the clinicopathological characteristics of microsatellite stable (MSS) and microsatellite unstable (MSI) colorectal cancers from Iran. n this study, we aimed to evaluate the clinicopathological and immunohistochemical findings of MSS and MSI colorectal cancers in our Center as the largest Center of gastrointestinal surgery and oncology in the South of Iran. We also compared the immunohistochemical method vs. molecular study using DNA sequencing.Methods: For 5 years (2015-2019), 34 patients who underwent operation in the affiliated Hospitals of Shiraz University of Medical Sciences were clinically suspected to microsatellite instability (MSI). The molecular diagnostic tests with DNA sequencing were performed. Clinicopathological and immunohistochemical findings of MSI colorectal cancers were compared with those who were stable. Results: In the South of Iran, MSI colorectal cancers were more common in males. These tumors were more common in the right side with more tendencies to produce mucin with lymphocytic infiltration. Conclusion: It was concluded that immunohistochemistry is a specific method for the diagnosis of MSI colorectal cancers, but false negative rate is high, and sensitivity is low. Therefore, we recommend performing molecular studies by DNA sequencing in colon cancer with clinical suspicion to MSI and negative immunohistochemistry